Analysis of the Influence of Growth Mindset, Fixed Mindset and Self Efficacy on Academic Grit in Industrial Engineering Students, Class of 2020, Faculty of Engineering, Pattimura University, Ambon - Yaniah, Samrotul; Lewaherilla, Novalien Carolina; Leuhery, Ferdy (Jurnal Ekonomi, 2024)
In today's era where technological advances and accelerated transformation require humans to have a mindset that can think critically and creatively in facing life's challenges. This acceleration shapes the character of each person. This character determines a person's decision in making decisions. The phenomenon that occurs is that the characteristics of students in determining decisions in their lectures are different. Not a little influence on the student's lecture period. This research was conducted on 50 Industrial Engineering Students Class of 2020 Pattimura University Ambon. Sampling in this study was carried out using saturated sampling techniques. then a questionnaire was made through a Google Form as many as 20 statements which were then processed using SPSS Software. This result is known by looking at the value of the partial test, of independent variables (Growth Mindset, Fixed Mindset, Self Efficacy) has a positive and significant effect on the dependent variable (Grit Academic).